Discussion of "Target's Tax Shelter Participation and Takeover Premiums"1. (4th June 2016) - Shevlin, Terry
Abstract: Chow, Klassen, and Liu (2016 ), hereafter CKL, examine whether M&A bidding firms are willing to pay more for target firms that disclose they have not participated in a "tax shelter" sometime in the past. My discussion provides an overview of the past and current tax literature in accounting and places CKL within this expanding literature. I then provide a critique of this interesting and well‐executed study that exploits an unusual disclosure to examine tax shelter participation effects.